Pengaruh Light Massage Terhadap Tekanan Darah Penderita Hipertensi Primer Di Kabupaten Banyumas - Sidik Awaludin; Arif Setyo Upoyo; Iwan Purnawan (Interest : Jurnal Ilmu Kesehatan, 2018)
Abstract : Blood Pressure, Light Massage, Hypertention. The impact of hypertension leads to heart attack, renal failure and stroke if the blood pressure is not controlled. Light massage is a complementary therapy for blood pressure control of patients with primary hypertension. Light massage can cause a relaxation response and reduce stress. The purpose of this study was to identify the effect of light massage on the decrease in blood pressure. Research design is pre experimental. The number of respondents in this study were 16 respondents. Sampling technique used is purposive sampling. The study was conducted by measuring blood pressure before and after light massage therapy. Blood pressure measurement using digital tensimeter. Test the difference in blood pressure before and after intervention using Wilcoxon test. The results showed a significant difference in blood pressure before and after treatment in the group receiving light massage therapy (p value 0.035). Light massage affects the decrease in blood pressure in patients with primary hypertension.